European Myeloma Network recommendations on tools for the diagnosis and monitoring of multiple myeloma: what to use and when - Caers, Jo; Garderet, Laurent; Kortüm, K. Martin; O’Dwyer, Michael E.; Donk, Niels van de; Binder, Mascha; Woerner, Sandra Maria; Gay, Francesca; Corre, Jill; Beguin, Yves; Ludwig, Heinz; Larocca, Alessandra; et al. (Haematologica, 2018)
The diagnosis of multiple myeloma can be challenging, even for experienced physicians, and requires close collaboration between numerous disciplines (orthopedics, radiology, nuclear medicine, radiation therapy, hematology and oncology) before the final diagnosis of myeloma is made. The definition of multiple myeloma is based on the presence of clinical, biochemical, histopathological, and radiological markers of disease. Specific tests are needed both at presentation and during follow-up in order to reach the correct diagnosis and characterize the disease precisely. These tests can also serve prognostic purposes and are useful for follow-up of myeloma patients. Molecular analyses remain pivotal for defining high-risk myeloma and are used in updated patient stratifications, while minimal residual disease assessment via flow cytometry, molecular techniques and radiological approaches provides additional prognostic information on patients’ long-term outcome. This pivotal information will guide our future treatment decisions in forthcoming clinical trials. The European Myeloma Network group updated their guidelines on different diagnostic recommendations, which should be of value to enable appropriate use of the recommendations both at diagnosis and during follow-up.
Gesehen am 26.03.2020